Homeland Comfort in an Alien Land: The Role of the Huiguan in Exclusion Era Los Angeles - Edwards, Christopher (The Toro Historical Review, 2019)
Chinese immigrants in the mid 1800’s faced legislative discrimination as well as a brutal race-riot to establish themselves in Los Angeles. The organizations called huiguans they had developed to support travelers in China played an important role in supporting them in America. These organizations helped Chinese immigrants face many obstacles in Los Angeles, including legal exclusion from emigrating to America.